Productivity increase in a cellular battery line using lean kaizen and tools - Brodie Murayama, Roberto Cartwright (2019)
Companies striving to compete in the market place, use many lean techniques to advance production and seek to achieve lower costs and higher competitiveness. The application of the Kaizen methodology, enticing a group of professionals to observe and analyze a problem, forward improvement suggestions and apply them, creates a new state on which further enhancements can be made. Together with the utilization of brainstorming and chrono-analysis tools, opportunities are identified and technically support the project. The work focused on a 5-week review of one manufacturing line that each day produced 833/h. Cylinder lithium cell batteries for mobile phone application. Yearly cost reduction of $15,000, with minimal $1.374 investment was achieved, resulting in 52.59% cycle time improvement.